DIGITAL COMPETENCE AND DATA LITERACY IN FRAUD DETECTION - Erfiansyah, Erfan; Bagianto, Agus; Al-Qowiyy, Hamiz; Husna, Laila (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2026)
Despite increasing digitalization in the accounting profession, limited empirical evidence explains how digital competence is transformed into effective fraud detection capability, particularly among early-career accountants. This study aims at examining the effects of digital competence and data science literacy on fraud detection skills, with diagnostic skills as a mediating mechanism among Generation Z accountants in Indonesia. Using a quantitative survey of 150 respondents and partial least squares structural equation modeling (PLS-SEM), the findings show that digital competence does not directly enhance fraud detection skills but operates through data science literacy and diagnostic skills. Diagnostic skills emerge as the key cognitive mechanism converting technological capability into fraud detection effectiveness. These results imply that accounting education and professional training should prioritize diagnostic reasoning alongside digital and analytical skills.